Detection and Management of Water Stress at Plants by Deep Learning and Image processing Case-study of Tomato - Guerbaoui Mohammed; Ichou Ismail; Bakziz Zakaria; Selmani Abdelouahed; El Faiz Samira; Ed-Dahhak Abdelali; Benhala Bachir; Lachhab Abdeslam (E3S Web of Conferences)
This project aims to develop an innovative technique for detecting water stress in tomato plants using deep learning and image processing techniques, and to integrate it into a mobile application for real-time monitoring. The methodology adopted includes the acquisition and preprocessing of image data, the construction and training of a deep learning model, and the development of a user-friendly mobile application. The results show a promising performance of the model in the precise detection of water stress, confirming the usefulness and usability of the developed mobile application.